The power of vision - Barker, Joel Arthur (Burnsville : Charthouse International Learning, 1993)
Mr. Barker shows why a positive vision of the future is essential for organisations and individuals who wish to shape their future
Keywords: Social prediction; Business forecasting; Forecasting